Tren dan Perkembangan Penelitian Kurikulum Pendidikan Islam: Perspektif Bibliometrik terhadap Pendidikan Berkualitas dan Inklusivitas dalam SDGs - Lis Safitri; Nurlaela; Musmuallim; Ulul Huda; Noor Asyik; Abdul Rohman (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study aims to analyze the trends and developments in Islamic education curriculum research during the past decade (2014-2024) through a bibliometric approach. Employing the Bibliometrix R package and VOSviewer, 616 Scopus-indexed documents were analyzed to identify publication patterns, scholarly collaboration, bibliographic coupling, thematic evolution, and keyword co-occurrence. The results indicated a notable rise in academic publications during the past decade, particularly from Indonesia, Malaysia, and the United Kingdom. Five main keyword clusters were identified, namely integration of Islamic education within the framework of educational reform, multicultural education, institutional practices, socio-cultural involvement, and curriculum development. Thematic evolution indicated that character education, multiculturalism, and Islamic identity were the basic themes, although topics like sex education and extremism exhibited a changing pattern facing global challenges. Despite the growing interest in these issues, bibliographic analyses reveal fragmented work and limited local citations. Additionally, the study highlights the increasing role of international collaborations in advancing Islamic education research and the growing focus on integrating contemporary societal issues within the curriculum. This research offers significant insights into the shifting focus areas within Islamic education, reflecting both regional and global academic trends, and suggests areas for further development in curriculum and educational practices. This research contributes to achieving SDG 4 by advancing understanding of how Islamic education can be aligned with global educational objectives, promoting a more inclusive and equitable approach to curriculum development.